Use of Intra-Community Acquisition’s Value and Quantity for Calculating Mirror Data Asymmetry in International Trade - Iwona MARKOWICZ; Paweł BARAN (Communications of International Proceedings, 2020)
The aim of the article is to compare two approaches to measuring the quality of international trade data. The specificity of these data lies in registering them in two sources, in the countries of trading partners. The authors study data discrepancies in transactions concerning the intra-Community exchange. Information about the size of this exchange is registered in the EU’s Intrastat system. A specific transaction is listed in one country as an intra-community supply of goods (ICS) and in the other country as an intra-community acquisition of goods (ICA). The compilation of this information indicates an asymmetry of data. The size of this asymmetry informs about the quality of statistical data. An important issue is the proper way of measuring this quality. In the literature, the approach using value indicators prevails, while the approach using quantity, expressed by weight of goods, is omitted. The authors conducted an empirical study in order to compare two variants of determining the aggregated data quality index. The example concerns Poland's transactions by commodity groups (CN chapters) with EU Member States (aggregation by country). The numerical example uses COMEXT data on intra-Community trade in 2017 provided by Eurostat.
Keywords: Intra-Community Trade; Asymmetry Data; Indicators of Mirror Data Quality